Improved Meet-in-the-Middle Attacks on Reduced-Round Kiasu-BC and Joltik-BC. (3rd July 2019) - Liu, Ya; Shi, Yifan; Gu, Dawu; Zeng, Zhiqiang; Zhao, Fengyu; Li, Wei; Liu, Zhiqiang; Bao, Yang
Abstract: Kiasu-BC and Joltik-BC are internal tweakable block ciphers of authenticated encryption algorithms Kiasu and Joltik submitted to the CAESAR competition. Kiasu-BC is a 128-bit block cipher, of which tweak and key sizes are 64 and 128 bits, respectively. Joltik-BC-128 is a 64-bit lightweight block cipher supporting 128 bits tweakey. Its designers recommended the key and tweak sizes are both 64 bits. In this paper, we propose improved meet-in-the-middle attacks on 8-round Kiasu-BC, 9-round and 10-round Joltik-BC-128 by exploiting properties of their structures and using precomputation tables and the differential enumeration. For Kiasu-BC, we build a 5-round distinguisher to attack 8-round Kiasu-BC with 2^109 plaintext–tweaks, 2^112.8 encrytions and 2^92.91 blocks. Compared with previously best known cryptanalytic results on 8-round Kiasu-BC under chosen plaintext attacks, the data and time complexities are reduced by 2^7 and 2^3.2 times, respectively. For the recommended version of Joltik-BC-128, we construct a 6-round distinguisher to attack 9-round Joltik-BC-128 with 2^53 plaintext–tweaks, 2^56.6 encryptions and 2^52.91 blocks, respectively. Compared with previously best known results, the data and time complexities are reduced by 2^7 and 2^5.1 times, respectively. In addition, we present a 6.5-round distinguisher to attack 10-round Joltik-BC-128 with 2^53 plaintext–tweaks, 2^101.4 encryptions and 2^76.91 blocks.